Impact of Preoperative Anemia on Perioperative Outcomes in Patients Undergoing Elective Colorectal Surgery - Liu Liu; Lin Liu; Li-Chuang Liang; Zhi-qiang Zhu; Xiao Wan; Heng-bing Dai; Qiang Huang (Gastroenterology Research and Practice)
Aim. To evaluate the impact of preoperative anemia (POA) on perioperative outcomes in patients undergoing elective surgery for colorectal cancer (CRC). Methods. A total of 326 CRC patients were enrolled. POA was defined as a hemoglobin (Hb) concentration ≤ 12 g/dl. Univariable and multivariable analyses were performed to assess the impact of POA on the risks of postoperative complications like surgical site infection (SSI). Results. Patients with colon cancer presented higher rate of POA than patients with rectal cancer (60% versus 40% for colon cancer versus rectal cancer). In addition, female patients and patients with large tumor mass (>4 cm) had a higher rate of POA than male patients and patients with small tumor (≤4 cm), respectively. Upon univariable analysis, CRC patients with POA had a higher rate of incisional SSI than patients without POA (12% versus 6%, P=0.04). However, POA was not associated with other postoperative complications, like anastomotic leak, organ space SSI, and bleeding. Upon multivariable analysis, POA and stoma formation were identified as two independent risk factors for incisional SSI (OR (95%CI): 2.44 (1.09–5.49) for POA versus no POA and 2.64 (1.20–5.81) for stoma formation versus no stoma formation). Conclusions. POA was an independent risk factor for incisional surgical site infection after colorectal resection for CRC, and correcting POA should be considered before elective surgery.